MODELING DYNAMIC SYSTEM FOR MANAGEMENT OF COASTAL AREA ECOSYSTEM OF KENJERAN TO HEAVY METAL CADMIUM (Cd) CONTAMINATION - Hasan, Imron; Zam Zam, Zulkifli (Green Earth, 2012)
The coastal area represents to a dynamic ecosystem, devided to the coastal land and coastal waters subsystem which each other interconnected. The ecosystem interconnected in environmental represents to a dynamic environmental systems process, where change that happened at one ecosystem will be influence and/or influenced by other ecosystem. The coastal area ecosystem of Kenjeran contaminated by heavy metal cadmium (Cd), its caused by development activity to both subsystem. To dissolve this problem, needed integrated and sustainable management of coastal area ecosystem with the system dynamic approach. This research aim are; (1) analysing amount heavy metals Cd from development activity (insudtrial) at Kenjeran channel, (2) analysing water, sediment quality at Kenjeran channel and water, sediment, bivalvia quality at Kenjeran estuary, and (3) modeling the management of coastal area ecosystem of Kenjeran with Vensim 5.0 software from High Performance System.Method of intake sample waters and sediment conducted to the integrated sampling system, while intake of sample bivalvia in Kenjeran estuary conducted to random. Hereinafter from concentration Cd data obtained, analysed by 2 way of, that is; (1) the statistically use ANOVA, and (2) comparing concentration Cd with water quality and industrial waste standard. Management of coastal area ecosystem of Kenjeran conducted to the system approach, modeling dynamic system to environmental, economic, and population aspect. From result obtained, that industrial waste of electroplating have the cadmium content of mean equaled to 0,0830 mg/ liter, waste of printing office industrial 0,0731 mg/liter, waste of plastic industrial 0,0060 mg/liter and waste of food indutrial 0,0066 mg/liter. The content of cadmium at stream water and sediment in channel of Kenjeran are 0,0295 mg/liter and 3,8056 mg/liter. While, cadmium content in Kenjeran estuary to each component are 0,0327 mg/liter at sea water, 0,4816 mg/liter at sediment and 0,2081 mg/liter at bivalvia. Scenario simulation of Early Model (without environmental expense) economical profit equaled to Rp. 294.525.000, however, environmental aspect there is tendency to the environmental degradation of coastal area of Kenjeran equaled to Rp. 21.870.000 at the last simulation (20 year) and is not self-financing. So that local government will be non-stoped ladened with the environmental management costs equaled to Rp. 179.633.000. Population increased every year progressively which at the last simulation equaled to 286537 people. It also had contribution to degradation area equaled to Rp.3.581.710. While, result of scenario simulation 1 (with the environmental expense) equaled to 20 %, yield the clean benefit value of economics activity equaled to Rp. 208.745.000 and the environmental degradation of became Rp. 2.551.420 at the last simulation (20 year). Keywords: Management, The coastal area ecosystem of Kenjeran, Dynamic System, Cadmium (Cd).